PENGEMBANGAN MEDIA PEMBELAJARAN ARTIFICIAL INTELLEGENCE PADA MATERI MENGENAL DAN MENGIDENTIFIKASI PUISI RAKYAT KELAS VII SMP - Mai Yuliastri Simarmata; Dewi Leni Mastuti; Rini Agustina (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
His study aims to examine the practicality of Artificial Intelligence learning media using ChatGPT for seventh-grade junior high school students. This study is a Research and Development (R&D) study with a population of seventh-grade students at SMP 3 Sungai Kakap, Kubu Raya Regency. The sample was taken from one class, namely the seventh grade. The sampling technique used was purposive sampling. The data collection techniques used were indirect communication and measurement. The tools used were expert validation sheets, questionnaires, and tests. The results of the study showed that the validation results of the artificial intelligence learning media using ChatGPT provided several notes for improvement, which later became the basis for improvements or revisions to the media that had been developed. The main points for improvement were in the aspects of presentation, content suitability, and language use to suit the students' interests. The level of practicality of the Artificial Intelligence learning media using ChatGPT in learning to recognize and identify folk poetry for Year 7 junior high school students was 84%, which is considered very practical. Based on the questionnaire results, it was found that the Artificial Intelligence learning media using ChatGPT that was developed was practical to use.